The first Amazonian species of Andranthobius Kuschel (Coleoptera: Curculionidae), with records of new host palms for the genus - Valente, Roberta De Melo; Da Silva, Paulo Augusto Lima (Zootaxa, 2014)
Andranthobius setirostris sp. nov. is the first species of Andranthobius Kuschel described from the Amazon. It is distinguished from other species within the genus by an anterior obtuse tubercle on the lateral margin of the pronotum, the rostrum of the males with a lateroventral row of tubercles and comb of setae, and a much larger body. Adult specimens were originally collected in flowers of the palms Syagrus vermicularis Noblick and Syagrus cocoides Mart., and additional collections suggest that this association is specific. Both species of palms are recorded for the first time as host plants of Andranthobius.